Automated fluorine-18 radiolabeling via an alkyne–azide cycloaddition reaction on a dual peptide-functionalized liposome surface for in vivo PET imaging - Iannone, Marco; Kravicz, Marcelo; Rainone, Paolo; Antoniou, Antonia I.; Stucchi, Stefano; Valtorta, Silvia; Amenta, Arianna; Turolla, Elia Anna; Pellegrino, Sara; Passarella, Daniele; Vino, Elisa; Todde, Sergio; et al. (Frontiers in Pharmacology, 2025)
IntroductionLabeled nanoparticles can be monitored in the body using positron emission tomography (PET) imaging, providing real-time insights into their pharmacokinetics and biodistribution. In the present work, liposomes are labeled with the radionuclide fluorine-18, exploiting a “surface radiolabeling” approach.MethodsTwo alkyne-dioleoylphosphatidylethanolamine (DOPE) constructs are embedded within the bulk of the liposome bilayer, which is composed of cholesterol (Ch) and sphingomyelin (SM), and radiolabeling is performed via either a copper(I)-catalyzed cycloaddition “click” reaction (CuAAC) or a cyclooctyne-driven copper-free “click” reaction (CyOctC) modality, using a suitable fluorine-18 labeled azide, obtaining good results in terms of yield, purity, stability, and automation of the entire radiosynthesis process. In addition, radiolabeling is also performed on liposome formulations functionalized with 1) a peptide derived from the receptor-binding domain of apolipoprotein E (mApoE) and 2) a metalloproteinase (MMP)-sensitive lipopeptide (MSLP). The in vivo uptake of these liposomes is evaluated in an orthotopic glioma mouse model (Gli36ΔEGFR cell line) using PET/computed tomography (CT).Results and discussionThe results demonstrate a higher tumor/background ratio, a faster clearance rate, and a lower uptake in healthy brain tissue and peripheral regions for mApoE- and MSLP-functionalized liposomes than for non-functionalized liposomes, prompting further characterization. On the contrary, radiolabeled liposome uptake is higher in the majority of peripheral organs for non-functionalized liposomes. Hence, fluorine-18-labeled liposomes can be reliably used for in vivo PET tracking of multifunctionalized nanoparticles, enabling effective investigation of their potential as drug delivery systems.